2006
DOI: 10.1111/j.1600-0404.2005.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible cochlear damage in myasthenia gravis - otoacoustic emission analysis

Abstract: It is clear that disease progression is associated with irreversible cochlear damage. Lack of improvement in patients' emissions despite partial non-audiometric improvement in relation to receptors needs to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In patients with MG, autoantibodies against AChRs were reported to bind with AChRs on OHCs, inducing a progressive loss of AChRs that decreases OHC electromotility [114]. This cascade of events induces apoptosis in all three rows of OHCs, evolving into a clinically evident SNHL in rare cases [115].…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with MG, autoantibodies against AChRs were reported to bind with AChRs on OHCs, inducing a progressive loss of AChRs that decreases OHC electromotility [114]. This cascade of events induces apoptosis in all three rows of OHCs, evolving into a clinically evident SNHL in rare cases [115].…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…CAS produces physiological suppression of otoacoustic emissions [117] protecting the hair cells from noise of moderate to high intensity [118]. A reduced CAS effect has been reported in patients with MG compared to control subjects, suggesting a possible role of the progressive reduction of beta subunits of nicotinic AChRs associated to the destruction of the basal membrane and OHCs due to prolonged exposure to autoantibodies [114, 116]. …”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The affected patients show hearing loss particularly to high frequency waves (above 30 decibels). A number of human studies have shown progression of MG associated with irreversible cochlear damage causing sudden loss in hearing (Arnold, 1997;Hamed et al, 2006). MG could cause non suppurative otitis media, leading to hearing loss (Brookler et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…However, they are major causes of morbidity and mortality. Other nervous system manifestations were also reported in some patients with MG as memory difficulties and cognitive impairment [15][16][17][18], autonomic dysfunction [19,20], sensorineural hearing loss [21] and psychiatric disorders [22] which are also related to sleep abnormalities with MG [7]. Several central (e.g.…”
Section: Introductionmentioning
confidence: 99%